Respuesta :
If you have to add two expressions 3.2x−6 and −5.6x+4 you have to add members with x to members with x and members without x to members without x.
[tex](3.2x-6)+(-5.6x+4) =(3.2x-5.6x)+(-6+4)=-2.4x-2[/tex].
Answer: -2.4x-2
[tex](3.2x-6)+(-5.6x+4) =(3.2x-5.6x)+(-6+4)=-2.4x-2[/tex].
Answer: -2.4x-2
Answer:
[tex]-2.4x-2 [/tex]
Step-by-step explanation:
We are given the expressions :
[tex]3.2x-6[/tex] ---a
[tex]-5.6x+4[/tex] ----b
We are supposed to add these two expressions to get the resultant
⇒ Expression a + Expression b = Resultant
⇒[tex]3.2x-6 +(-5.6x+4) [/tex]
⇒[tex]-2.4x-2 [/tex]
Thus the resultant is [tex]-2.4x-2 [/tex]
Hence , the addition of the given expressions in simplified form is [tex]-2.4x-2 [/tex]